2006
DOI: 10.1243/09544119jeim117
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on stick phenomena in metal-on-metal hip joints after resting periods

Abstract: Insufficient understanding of tribological behaviour in total joint arthroplasty is considered as one of the reasons for prosthesis failure. Contrary to the continuous motion input profiles of hip simulators, human locomotion contains motion interruptions. These occurring resting periods can cause stick phenomena in metal-on-metal hip joints. The aim of the present study was to investigate the tribological sensitivity of all-metal bearings to motion interruptions on in vitro test specimens and retrieved implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
(12 reference statements)
3
28
2
Order By: Relevance
“…As was shown earlier,23 thick denatured protein layers might stick rigidly onto the passive layer of cobalt alloys. Because chromium‐oxide forms in a moist environment, this is expected and was verified using XPS (data not shown).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…As was shown earlier,23 thick denatured protein layers might stick rigidly onto the passive layer of cobalt alloys. Because chromium‐oxide forms in a moist environment, this is expected and was verified using XPS (data not shown).…”
Section: Resultssupporting
confidence: 58%
“…In turn, these complexes are adsorbed onto the metallic surfaces 35. These protein layers adhere rigidly to the surfaces23 and are typically found on passive metal films 17…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the larger diameter bearing generated a lower friction factor than the 28 mm bearing under all test conditions, although this was not significant. This differs from Wimmer et al [10] who assumed a similar friction factor for metal-on-metal bearings with different diameters. Such a discrepancy can be readily explained from the fluid-film lubrication contribution.…”
Section: Discussioncontrasting
confidence: 56%
“…In vitro studies have demonstrated the low-wearing behaviour of the metal-on-metal bearing [7,8], and clinical studies have also demonstrated favourable results [9]. The frictional torques generated within the new generation bearings are less than those required to cause mechanical loosening [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The torques calculated in this study act in the medial lateral (frontal) plane, which is perpendicular to the frictional torque due to flexion extension movement in the anterior-posterior plane. 22,23 The relative stability of the cup and resistance to loosening in these two planes are not known. Head-rim contact and edge loading may also cause micro-motion of the cup, which may give rise to increased cup inclination, and subsequently affect head-rim contact and further the stability of the fixation.…”
Section: Discussionmentioning
confidence: 99%